PENGARUH KEMAMPUAN PENALARAN MATEMATIS DAN MINAT BELAJAR TERHADAP HASIL BELAJAR - Nanda Karina Tegarwati; Nuryani, Eva; Warniasih, Kristina (LPPM Universitas Advent Indonesia, 2024)
The purpose of this study was to determine the effect of mathematical reasoning ability and student interest in learning on student learning outcomes. This research was conducted at SMP N 7 Yogyakarta in the 2023/2024 school year. Sampling in this study used the Simple Random Sampling technique and obtained the research samples, namely class VII B and VII C. This type of research is correlational research. Data collection used in this study was a description test and questionnaire. The data analysis technique used multiple linear regression analysis to determine the effect of mathematical reasoning ability and student learning interest on student learning outcomes. The results concluded that mathematical reasoning ability (X1) and interest in learning (X2) simultaneously (together) affect learning outcomes (Y) by 19,5%. While the rest is influenced by variables that are not studied.